Processo argumentativo na (re)significação de concepções ético/morais - Aguiar, Joelma Gomes de (2006)
This study analysed the relationship between the production of argumentative discourses and the development and (re)signification of ethical/moral concepts, conceptions and reasoning. It focused on ethical-argumentative reasoning concerning other people and their different points of view. The specific aims of this research were: (1) to investigate the considering alternative positions on adolescents previous views on a specific topic; (2) to verify whether the ability to generate counterarguments was associated with higher levels of moral reasoning, according to Kohlberg theory, and (3) to have a better comprehension of a possible relationship between adolescents abilities to use cognitive and verbal-argumentative strategies and the (re) signification of concepts/beliefs of an ethical/moral nature, and also the solution of conflicts of the same nature. The participants in this study were seventh grade students of private and public schools. Four empirical tasks were used in order to evaluate argumentative and moral reasoning. These tasks focused on: the evaluation of moral dilemmas (DIT); the evaluation of moral dilemmas with the presentation of a written justification for subjects responses; the production of arguments and the reaction to counterarguments. There was also a group-debate situation in which both argumentation and the discussion ethical/moral issues were observed. The moral dilemmas tasks aimed to evaluate the level of moral reasoning of the participants. The argumentation tasks investigated whether the adolescents generated and justified a point of view and how they dealt with counterarguments or alternative information which could lead the participants to modify their initial positions on the topic under discussion in a monological situation as well as in a group-debate setting. The results showed that, in a monological situation, most of the adolescents produced only a partial developed argumentative discourse, whereas in a more social-verbal interaction situation their discourse appeared to be more elaborated. As a general result, it was observed that the confrontation with the other s views, or dealing with counterarguments allow the adolescents to re-evaluate and re-elaborate their own views on a debatable topic. Regarding the relationship between counterargumentation and moral reasoning, it was verified that there was a subtle tendency associating the two processes. However, other factors, such as, social, emotional and cultural aspects might also influence the development of moral reasoning